Speech of order - Trelles, J. O. (1952)
We have seen these days in honor of Cajal to a magnificent exhibition of his work, his life, his glory. We congratulate Dr. Juan Francisco Valega, President of nnuestra Company for the successful initiative to organize this celebration, and for having done so brilliantly. For my part, I thank you deeply for giving me the opportunity, flattering and honorable, to draw very roughly the suggestive theme "neurological Cajal in contemporary thought."